DEGRADASI RHODAMIN B SECARA FOTOKATALISIS DAN OZONOLISIS DENGAN PENAMBAHAN TIO2-NIFE2O4, TiO2-CuFe2O4, DAN TiO2-MnFe2O4 - Safni -; Deliza -; Rahmayeni - (Jurnal Riset Kimia, 2014)
Vol 7 No 2ABSTRACTDegradation of Rhodamin B has been done by photocatalytic and ozonolysis using TiO2-Anatase and TiO2-NiFe2O4, TiO2-CuFe2O4, TiO2-MnFe2O4 catalysts, photocatalytic methodused lamp with Î» = 365 nm and ozonolysis methode used ozon reactor. Analysis of degradationresult used spectrofotometer UV-Vis. TiO2-NiFe2O4, TiO2-CuFe2O4, TiO2-MnFe2O4 catalystwere characterized by XRD to determine size and structure of crystal. The solution ofRhodamin-B 2 mg/L was degraded 93,33 % without catalyst after being photolysed for 180minutes and after adding 0,02 g TiO2-MnFe2O4, TiO2-CuFe2O4, TiO2-Anatase, TiO2-NiFe2O4catalyst. The additional consentration in a row are 99,55 %; 99,77 %; 100 %; 100 %. Thesolution of Rhodamin B 2 mg/L was degraded 99,33% without catalyst after being ozonolysisfor 25 minutes and after adding 0,02 g of TiO2- MnFe2O4, TiO2-CuFe2O4, TiO2-Anatase, TiO2-NiFe2O4 catalysts with the additional consentration in a row are 99,77 %, 99,77 %, 99,77 %,100 %. So the degradation of Rhodamin B using ozonolysis method was faster thanphotocatalytic with catalysts and without catalyst.Keywords: Rhodamin B, Photocatalytic, Ozonolysis, TiO2-Anatase, TiO2-NiFe2O4, TiO2-CuFe2O4,TiO2-MnFe2O4.